(3eNJUQ cJGH GdGYJeGO aj GdCOhjI GdeaQOIs - (3GHf GdLRGQ , CMeO Hf EHQGgje Hf CHj NGdO GdbjQhGfj, CHh LYaQ,J (B369 (3g` s
(3ChdgG (B:s
(3MQa GdCda (B: (3CeHSfJjf gh CajMhGf dg hQb s
(3BNQgG (B:s
(3hai CWQGa GdMH THjg GdShGc hGdeSJYed efgG CZUGfgG hhQbgG hThcgG hgj EPG LaJ HbjJ HNVQJgG GfJgi HGNJUGQ ef cJGH GdEYJeGO ai GdCOhjI GdeaQOI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B137s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3GdWHs